An integrated perspective on code-mixing patterns beyond doubling?. Issue 5 (11th February 2016) - GULLBERG, MARIANNE; PARAFITA COUTO, M. CARMEN
Abstract : Code-mixing (CM) is a striking example of how two languages are active simultaneously in bilingual production. Gradient Symbolic Computation (GSC) proposes a formalism to account for the systematicity of CM patterns by integrating psycholinguistic notions of bilingual co-activation with generativist accounts of grammar. We applaud the attempt to bridge research traditions and all efforts to capture the systematicity of variation, and the interaction between processing and grammatical constraints in bilingual production. However, the descriptive and predictive scope of the current proposal remains somewhat unclear, as does its connection to existing accounts.